The Influence of Control Parameters on Precision of Welding Seam Tracking in Manually Control Master-slave Robot Remote Welding System. Issue 1 (1st March 2022) - Chen, Hongtang; Ma, Haijun; Jiang, Hongli; Lv, Shenjin; Li, Yong; Liu, Heshan
Abstract: The welding seam tracking precision is one of the key factors to ensure welding qua ntity. However, when the operator manually manipulate the master robot to control the slave ro bot tracking welding seam used the master- slave robot remote welding system, seam tracking precision does not meet the requirement of the welding quantity, the influence of control param eters on precision of welding seam tracking is unkown. In this article, a master-slave robot rem ote welding system is set up which includes a master robot with 6 degrees of freedom, a compu ter control system, and robot HP3J carrying a welding torch and laser sensor system. The slave robot tracking welding seam was controlled by computer control system and the human operat or via master manipulator. The influence of control parameters (cross deviation, arc length and welding speed) on precision of welding seam tracking was analysed. The experiment results de monstrate the more control parameters of operator, the lower tracking precision, so in order to guarantee a good welding seam tracking effect, the operator should control less parameters.